TECHNOLOGY TRANSFORMATION, FINANCIAL LITERACY, AND GOOD CORPORATE GOVERNANCE IN STRENGTHENING FINANCIAL PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW OF MSMES AND THE FINANCIAL SECTOR - Ayem, Sri; Febriyani, Rahma; Fadia, Nalaya Anggi; Desviani, Dini; Lahura, Anggelina; Kaka, Regina Ambu (LPPM Univ. Ibn Khaldun Bogor, 2026)
Abstract. This study aims to map the role of technological transformation, financial literacy, and Good Corporate Governance (GCG) in strengthening financial performance in MSMEs and the financial sector through the Systematic Literature Review (SLR) method. Using the PRISMA protocol, 29 articles from the Google Scholar, Crossref, and ScienceDirect databases for the period 2020–2025 were systematically analyzed. The results of the study show a relatively consistent pattern of findings that financial literacy and technological transformation have a positive effect on business performance and sustainability. However, the implementation of GCG still faces challenges at the MSME level due to limited resources, while in the financial sector, GCG has been proven to strengthen accountability despite variations in its impact on profitability ratios. The inconsistency of results in several studies indicates empirical gaps influenced by human resource capacity and regional characteristics. This study provides a theoretical contribution in the form of an integrative conceptual framework and practical advice for policymakers to optimize the digital ecosystem and governance education to improve the competitiveness of the MSME and financial sectors.